Perceived incongruity of gender and leadership roles: experiences of top women leaders in Malaysian sports associations - Aman, Mirian Pabatao; Yusof, Aminuddin; Mohamed Razali, Abu Bakar; Omar Dev, Roxana Dev (Human Resource Management Academic Research Society, 2019)
This study investigates the experiences of top women leaders in Malaysian sports associations with regard to discrepancy of gender and leadership roles, organizational discrimination, and pipeline problem in sport organizations. Data were collected through in-depth, face to face semi structured interviews, observations and document analysis involving seven women leaders in national sport organizations. The theme that emerged from the data was "experiences" related to the discrepancy of gender and leadership roles, organizational discrimination and leadership pipeline problem. These experiences result in the bias judgment against women as leaders, being denied of access, less supported and women being denied access to leadership positions. The results were discussed using the role congruity theory, homologous reproduction and pipeline problem. The findings in this study concluded the prejudices within the sporting system of the country contribute to the diminishing number of women role models because they opt to get out from the system than to embroil themselves into the situation. Consequently, there is a higher possibility for a fewer aspiring women leaders to pursue for leadership position.